INSURANCE FRAUD ESTIMATION: MORE EVIDENCE FROM THE QUEBEC AUTOMOBILE INSURANCE INDUSTRY - Caron, Louis; Dionne, Georges (Assurances, 1997)
This article follows a previous study on insurance fraud in the Quebec automobile insurance industry (Dionne and Belhadji, 1996). Results from that research showed that 3 to 6.4% of all claim payments (excluding those for "glass damage only") contained fraud, representing 28 to 61 million dollars in 1994-1995. This evaluation was a minimum since it was limited to observed fraud only. In this paper, we apply a statistical method to estimate the total fraud level in the industry for the same period. Our results show a multiplicative factor of 3.4% of fraudulent files found in Dionne and Belhadji, which means that total fraud payments ranged from 96.2 to 208.4 million dollars in 1994-1995. Our Best Guess Estimator yields roughly a 10% fraud rate or about 113.5 million dollars. An interesting corollary in this finding is that the claim adjusters who participated to the survey (representing 70% of the market), observed only 1/3 of the potential frauds in the studied closed files. One can interpret this number as an index of efficiency for the entire verification process in the industry. A natural question is: Why is this index of efficiency so low?